2016
DOI: 10.1038/ncomms11746
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced substrate steering and reshaping of [Ag2(H)]+ scaffold for selective CO2 extrusion from formic acid

Abstract: Metalloenzymes preorganize the reaction environment to steer substrate(s) along the required reaction coordinate. Here, we show that phosphine ligands selectively facilitate protonation of binuclear silver hydride cations, [LAg2(H)]+ by optimizing the geometry of the active site. This is a key step in the selective, catalysed extrusion of carbon dioxide from formic acid, HO2CH, with important applications (for example, hydrogen storage). Gas-phase ion-molecule reactions, collision-induced dissociation (CID), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 53 publications
(63 reference statements)
4
82
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In contrast, only a handful of examples of silver-catalyzed hydrogenation and hydrosilylation are known. [15][16][17][18][19][20] For example, AgOTf has been shown to catalyze the hydrosilylation of aryl aldehydes in the presence of Me 2 PhSiH and PEt 3 . 16 Similarly, the semihydrogenation of alkynes by a heterobimetallic Ag/Ru catalyst has been reported.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In contrast, only a handful of examples of silver-catalyzed hydrogenation and hydrosilylation are known. [15][16][17][18][19][20] For example, AgOTf has been shown to catalyze the hydrosilylation of aryl aldehydes in the presence of Me 2 PhSiH and PEt 3 . 16 Similarly, the semihydrogenation of alkynes by a heterobimetallic Ag/Ru catalyst has been reported.…”
mentioning
confidence: 99%
“…Although much progress has since been made in constructing a wide range of MOF catalysts, the vacuum like environment within MOFs suggested to us a tantalizing new concept for the design of novel MOF based catalysts, where gas‐phase studies are used to examine the likely reactivity of a catalytic metal site within a MOF (Scheme ). The use of gas‐phase models seemed plausible given that our previous reaction‐mechanisms approach, where gas‐phase studies using multistage mass spectrometry experiments (MS n ) in an ion trap are blended with DFT calculations, was successfully applied to the design of new catalysts from the ground up and the invention of new reactions for use in organic synthesis . In the former studies, through a sequence of iterations in which different ligands and metal sites were evaluated, we developed a series of ligated binuclear coinage metal hydride cationic catalysts for the selective decarboxylation of formic acid (Scheme a, b), a reaction of considerable interest for the use of formic acid in hydrogen storage applications .…”
Section: Introductionmentioning
confidence: 99%
“…In all cases a two‐step catalytic cycle operates (Scheme a) in which the metal hydride complex, 1 , reacts in Step I with formic acid to liberate hydrogen and form a coordinated metal formate, 2 , which in Step II liberates CO 2 under conditions of collision‐induced dissociation (CID). For these first generation catalysts the best ligand for the silver hydride was 1,1‐bis(diphenylphosphino)methane (dppm) to give complex 1 a (Scheme b), and solution phase studies confirmed the liberation of H 2 and CO 2 at a relatively low temperature of 65 °C . Although the exact nature of the stoichiometry of the solution phase catalysts is unknown, subsequent gas phase studies highlighted that tetranuclear silver hydride cluster complexes were unreactive towards formic acid .…”
Section: Introductionmentioning
confidence: 99%
“…Here we use a combination of theory and gas‐phase experiments to establish the requirements to “heterogenize” our recently designed phosphine ligated coinage metal hydrides for the catalytic and selective gas‐phase decomposition of formic acid into carbon dioxide and hydrogen [Eq. ], a reaction crucial for the use of formic acid in hydrogen storage applications trueHCO2normalHnormalH2+CO2 …”
Section: Introductionmentioning
confidence: 99%
“…Decarboxylation of [(L)M1M2(O 2 CH)] + by collision‐induced dissociation (CID) regenerates the catalyst [(L)M1M2(H)] + (Scheme , step II). The nature of the bisphosphine ligand, metal and stoichiometry were all found to play key roles, with [(dppm)Cu 2 (H)] + (dppm=1,1‐bis(diphenylphosphino)‐methane) emerging as the most effective catalyst …”
Section: Introductionmentioning
confidence: 99%